1981
DOI: 10.1093/bja/53.10.1039
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Platelet Aggregation and Increased Bleeding Time During General Anaesthesia With Halothane

Abstract: A significant correlation was found between the inhibition produced by 1% halothane with nitrous oxide and oxygen on platelet aggregation in vitro and the increase in bleeding time during anaesthesia with halothane, nitrous oxide and oxygen in 10 patients. It is suggested that halothane in nitrous oxide with oxygen inhibits platelet aggregation in vivo and in vitro. The inhibition is not seen when platelet aggregation is studied in platelet-rich plasma from anaesthetized patients because the agents evaporate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 2 publications
1
10
0
2
Order By: Relevance
“…Previous investigators have demonstrated the anti-aggregatory effects of halothane in vitro 1-4 and in vivo. s-8 Dalsgaard-Nielson et al 6 showed that platelet aggregation is affected in blood obtained during halothane anaesthesia, which resulted in prolongation of bleeding time. Gibbs 7 demonstrated that isoflurane, in contrast to halothane, did not affect platelet function ex vivo.…”
mentioning
confidence: 99%
“…Previous investigators have demonstrated the anti-aggregatory effects of halothane in vitro 1-4 and in vivo. s-8 Dalsgaard-Nielson et al 6 showed that platelet aggregation is affected in blood obtained during halothane anaesthesia, which resulted in prolongation of bleeding time. Gibbs 7 demonstrated that isoflurane, in contrast to halothane, did not affect platelet function ex vivo.…”
mentioning
confidence: 99%
“…Sevoflurane and propofol have an inhibitory effect on intraoperative and early postoperative platelet aggregation, but isofturane has no effect on platelet aggregation [6]. Dalsgaard-Nielsen et al [5] also reported that halothane increases bleeding time. Based on these results, isoflurane can be recommended as an inhaled anesthetic for such research.…”
Section: Discussionmentioning
confidence: 99%
“…Der Einfluss von volatilen und intravenösen Anästhetika auf die Thrombozyten ist dabei nicht auszuschlieûen. Dalsgaard-Nielsen et al [1] fanden eine um 54 % verlängerte Blutungszeit während einer Anästhesie mit Halothan. In einer Studie von Fyman et al [2] war die Blutungszeit durch Halothan im Gegensatz zu Enfluran und Isofluran ebenfalls verlängert.…”
Section: Introductionunclassified